Enterprise education - Enstroem, Rickard (My University, 2026)
Enterprise education equips individuals with the attributes, competencies, and behaviors necessary to navigate and succeed in diverse professional environments. This chapter explores the historical evolution, core components, and methodologies of enterprise education. Enterprise education bridges the gap between formal education and real-world applications by integrating experiential learning and work readiness frameworks. The chapter also highlights effective classroom strategies and measurement tools that assess the impact of enterprise education on student outcomes.
Keywords: behavioral outcomes; business education; competencies; decision-making; educational frameworks; enterprising education; experiential learning; personal attributes; professional competencies; resilience; strategic thinking; transversal competencies; work readiness